Are Articular Cartilage Lesions and Meniscus Tears Predictive of IKDC, KOOS, and Marx Activity Level Outcomes after ACL Reconstruction? A 6-Year MOON Cohort Study - Cox, Charles L. (Orthop J Sports Med, 2013)
OBJECTIVES: Identifying risk factors for inferior outcomes after ACL reconstruction (ACLR) is important for prognosis and future treatment. Study goal: analyze a sufficiently large enough cohort to evaluate whether articular cartilage and meniscal variables are predictive of three validated sports outcome instruments. We hypothesized that articular cartilage lesions and meniscus tears/treatment would be predictors of IKDC, KOOS (all 5 subscales), and Marx Activity Level at 6 years after ACLR. METHODS: From 2002-2004, 1411 ACLR subjects were prospectively enrolled and followed longitudinally with the IKDC, KOOS, and Marx completed at entry, 2 and 6 years. A logistic multivariable model consisted of patient demographics, surgical technique variables, and articular cartilage injuries and meniscus tears/treatment for determining predictors (risk factors) of IKDC, KOOS, and Marx at 6 years. RESULTS: We completed a minimum follow-up on 93% (1307/1411) of our cohort at 6 years. Baseline results: 56% male, median age 23 years, 75% with non-contact injury mechanism, articular cartilage pathology (MFC-25%, LFC-20%, MTP-6%, LTP-12%, patella-20%, and trochlear-9%), and meniscal pathology (medial-38%, lateral-46%). Both articular cartilage lesions and meniscal tears significantly predicted 6 year outcomes on IKDC and KOOS (Table 1). Grade 3 or 4 articular cartilage lesions (excluding patella) significantly reduced IKDC and KOOS scores at 6 years. Figure 1 focuses on IKDC and demonstrates worse outcomeswith chondral injuries on the MFC, MTP, and LFC. Likewise, KOOS was negatively affected by cartilage injury. The sole significant predictor of reduced Marx activity was the presence of a grade 4 lesion on the MFC. Lateral meniscus repairs did not correlate with inferior results, but medial meniscus repairs predicted worse IKDC and KOOS scores. Lateral meniscus tears left alone significantly improved prognosis. Small partial meniscectomies (<33%) on medial meniscus fared worse, but conversely, larger excisions on lateral meniscus (>50%) improved prognosis. Analogous to previous studies, other significant predictors of worse outcome scores were lower baseline scores, higher BMI, lower education level, smoking, and revisions. CONCLUSION: Both articular cartilage injury and meniscal tears/treatment at the time of ACLR were significant predictors of both IKDC and KOOS scores at 6 year follow-up. Similarly, having a grade 4 MFC lesion significantly reduced a patient’s Marx activity level score at 6 years.